Cerebrovascular diseases in Poland—inconsistent seasonal patterns of hospitalisation and mortality. (13th September 2017) - Poznańska, Anna; Wojtyniak, Bogdan; Chwojnicki, Kamil; Lewtak, Katarzyna; Rubikowska, Barbara; Seroka, Wojciech
Abstract: Background: A seasonal variation in the incidence of cerebrovascular diseases still remains inconsistently evidenced. Herein, we analyse the monthly patterns of two health phenomena: hospital admissions and deaths due to these diseases. Methods: We identified 69 511 cases of hospital admissions and 14 956 deaths due to cerebrovascular diseases (ICD10: I60-I69 and G45) among the inhabitants of five Polish voivodeship capitals in 2004–13. The method of time series analysis (exponential smoothing with linear trend and monthly additive seasonality) was applied to calculate the monthly specific seasonal indices. The monthly variation in an in-hospital fatality and nonhospital deaths were also analysed. Results: A summer season reduction in number of cases was observed for hospital admissions and deaths. Interestingly, the winter season effect is much more complex, mainly due to the contribution of December, when a high mortality is accompanied by a substantial decrease in the hospitalisation level. This unique discrepancy was observed for all the studied cities. Moreover, this month is characterised by a notably high in-hospital fatality. However, neither the number of non-hospital deaths nor the average length of hospital stay or the kind of hospitalised diseases evidenced that cerebrovascular problems were more serious in December than in any other month. Conclusion: The obtained results confirmed a seasonal variation in cerebrovascular diseases among the inhabitants of Polish cities. Habitual and administrative limitations in hospital activities observed every December do not seem indifferent from the patient health's perspective since they may lead to a low hospitalisation level and a high in-hospital fatality.